Influence of production parameters on the roughness of orthodontic ABS models manufactured via additive manufacturing - Lourenço Júnior, Ernesto; Cruz Neto, Rubelmar Maia de Azevedo; Mendonça, Rannier Marques; Alves, Antonio do Nascimento Silva; Casanova, Jaime (Brazilian Journal of Production Engineering, 2023)
Additive manufacturing (AM) has a strong impact in the dental field, offering advantages in productivity, cost, and customization of various products. Among the AM techniques, fused deposition modeling (FDM) has great application in the production of orthodontic molds (OM) compared to traditional techniques. However, the roughness of OM (orthodontic molds) produced by FDM is higher when compared to the pieces obtained through alginate molding. Therefore, evaluating the influence of FDM manufacturing parameters on roughness is of great importance. For this purpose, the experimental design methodology was used with the aim of determining which factors have a significant effect on OM roughness. Among the results obtained, layer height (LH) is the most influential factor in the roughness of the incisor element. For the canine and molar elements, the extruder nozzle diameter (END) is the most influential factor in roughness with an interaction between END and LH. Therefore, to aim for better roughness control in OM produced via AM, parameters such as layer height, extruder nozzle diameter, and filling percentage should be controlled.